Analysis of the Level of Service Quality Towards the Implementation of the Cleanliness, Beauty and Order (K3) Program in Jaya Baru District - Emsa, Tasmiati; Berutu, Noni Krisdayanti; Badruzzaman (Dinasti International Journal of Digital Business Management, 2023)
The Banda Aceh City Cleanliness and Beauty Environmental Service (DLHK3) has a task in public services, namely handling the problem of city waste, but the waste problem has not been fully resolved. The purpose of this study is to determine the level of community quality and waste management in the implementation of the Cleanliness, Beauty, and Order (K3) program in Jaya Baru District. This study uses a qualitative method, data collection through interviews, observations and documentation studies. The results of the study are the level of community quality towards the implementation of the Cleanliness, Beauty, and Order (K3) program is quite satisfactory, the speed of access to complaints made via the web, telephone, email and even social media to help the community so that complaints can be handled quickly. DLHK3 guarantees cleanliness services in Banda Aceh City by placing officers who have knowledge and ethics of politeness in each division. Division of areas/zones for cleaning officers in each zone and providing communal containers and containers that are spread across several locations in the Banda Aceh City area. Waste management is carried out by collecting and transporting waste with three operational hour zones at 06.00 to 10.00 (zone I), at 08.00 to 12.00 (zone II) and at 20.00 to 24.00 (zone III). DLHK3 carries out waste sorting using the 3R management method "Reduce, Reuse, Recycle" This waste management is carried out to distinguish between organic waste and inorganic waste. Environmental waste management, DLHK3 also carries out the Waste Collecting Point (WCP) method, namely sorting waste from its source, using a collection schedule, supervision, coaching of village cleaning/sanitation officers and special transportation according to the type of waste.